“Because of we are immigrants”: A focus group discussion on barriers related to maternal healthcare access among immigrant women in Kota Kinabalu, Sabah - Zulkhairul Naim Sidek Ahmad; Abdul Rahman Ramdzan; Mohd Jamsari Hashim; Muhammad Kamil Che Hassan; Dg Marshitah Pg Baharuddin (Zes Rokman Resources, 2021)
Compromised access to maternal health facilities among immigrants contribute to the increased prevalence of maternal mortality and morbidity. By understanding barriers to healthcare access among this group can create culturally appropriate interventions for improved health outcomes to the mother and newborn baby. Despite this, the research on these areas is very limited. Focus group discussions can be used to identify key barriers among this group. This study addresses this gap by exploring the key factors on barriers related to maternal healthcare access among immigrant women in Kota Kinabalu, Sabah in order to inform future recommendations. A qualitative study was conducted in September 2021 in selected areas in Kota Kinabalu, Sabah. Focus group discussion was carried out for collecting data. Interviews were audio recorded, transcribed, and analysed according to the themes that emerged. A total of 10 immigrant women in the reproductive age group were included in this focus group discussion. This study found that respondents in this study often felt that pregnancy related problems were important to address. Three major themes emerged from the qualitative analysis. Important themes include 1) no legal documents, 2) economic and financial factors and 3) cultural beliefs. In addition, this study found that the population was more likely to access private care than public facilities. This study has identified immigrant women as a vulnerable population subgroup in terms of maternal health utilization. This study suggests that simple, culturally appropriate health programs should be provided to women and communities to generate awareness about maternal health.